A study of e-commerce adoption by tourism websites in China. Issue 3 (September 2016) - Cao, Kaijun; Yang, Zhaoping
Abstract: Planning and booking a trip online is now increasingly common for travelers. This study evaluated 258 Chinese tourism websites (CTWs) using a content analysis technique that assessed website performance in terms of e‐commerce adoption. The current study aims to elucidate the status of e‐commerce adoption among different types of websites. The analysis revealed significant differences in performance between the types of websites, and online travel agencies (OTAs) were found to perform better than other types of tourism websites. The results also revealed that CTWs are not using the Internet to its full potential, as most tourism websites focus on providing basic information services, especially the official tourism websites (OTWs). Suggestions are made concerning how to improve the performance of CTWs and potential avenues for future research are discussed. Highlights: Uses content analysis to evaluate tourism website performance in terms of e-commerce adoption. Reveals significant differences in performance between the types of websites. Chinese tourism websites are not effectively utilizing the Internet to its full potential.